2019
DOI: 10.1111/dom.13829
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of linagliptin to improve glucose control in older people with type 2 diabetes on stable insulin therapy: A randomized trial

Abstract: Aim To assess the addition of linagliptin as an alternative to insulin uptitration in older people with type 2 diabetes on stable insulin therapy. Materials and Methods This phase 4, randomized, multicentre, double‐blinded, placebo‐controlled, 24‐week study recruited individuals on stable insulin, with baseline HbA1c 7.0%‐10.0%, aged ≥60 years and body mass index ≤45 kg/m2. HbA1c and fasting plasma glucose were measured at study visits, and participants assessed glycaemic control with a self‐monitoring blood g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 39 publications
5
33
0
1
Order By: Relevance
“…Conversely, more patients receiving linagliptin vs. placebo had their insulin dose reduced during the study. These trends were consistent at 24 and 52 weeks (Supplementary Table 3) and mirror the results from the global study [25].…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…Conversely, more patients receiving linagliptin vs. placebo had their insulin dose reduced during the study. These trends were consistent at 24 and 52 weeks (Supplementary Table 3) and mirror the results from the global study [25].…”
Section: Resultssupporting
confidence: 85%
“…In terms of glycaemic control and risk of hypoglycaemia, the results from the Japanese study at 24 and 52 weeks were consistent with the results from the global study, which was only conducted for 24 weeks [25]. In line with the results from the global study, linagliptin vs. placebo was effective in helping participants in the Japanese study population to achieve significantly lower levels of HbA1c; this finding was confirmed at both 24 and 52 weeks.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations